2020
DOI: 10.1097/01.aog.0000663412.67347.6b
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Early Pregnancy Has a Stronger Association to Pre-eclampsia and Diabetes Than Weight Gain [28D]

Abstract: INTRODUCTION: To evaluate the association of obesity in early gestation and weight gain during pregnancy to pre-eclampsia, pre-gestational and gestational diabetes rates. METHODS: We conducted a retrospective cohort study at our center from January 2013 to December 2015. Women with singleton pregnancies, who started prenatal care at less than 20 weeks, and who completed delivery at our center were included. The primary outcome was pre-eclampsia. Seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Assessment and care options will depend on the clinical circumstances, the presence of comorbidities, and the resources and services available at each healthcare facility. Roman et al [17] concluded that obesity is more important than GWG in the development of pre-eclampsia and GDM and refer to the importance of pre-conception weight reduction and counselling, in reducing morbidity in pregnancy. However, a meta-analysis of the association between GWG and adverse maternal and neonatal outcomes, was related to the risk of complications in pregnancy, weight retention and obesity in the offspring [23].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment and care options will depend on the clinical circumstances, the presence of comorbidities, and the resources and services available at each healthcare facility. Roman et al [17] concluded that obesity is more important than GWG in the development of pre-eclampsia and GDM and refer to the importance of pre-conception weight reduction and counselling, in reducing morbidity in pregnancy. However, a meta-analysis of the association between GWG and adverse maternal and neonatal outcomes, was related to the risk of complications in pregnancy, weight retention and obesity in the offspring [23].…”
Section: Discussionmentioning
confidence: 99%